2019
DOI: 10.1128/aac.02205-18
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preexisting Hepatitis C Virus Genotype 6 NS3, NS5A, and NS5B Polymorphisms on theIn VitroPotency of Direct-Acting Antiviral Agents

Abstract: HCV genotype 6 (GT-6) is found predominantly in East and Southeast Asia. Clinical studies have focused on patients infected with hepatitis C virus (HCV) GT-6a, where high sustained virologic response (SVR) rates to direct-acting antivirals (DAAs) have been achieved. However, GT-6 is highly diverse, with 29 reported subtypes. We explored the diversity of GT-6 polymorphisms at residues associated with DAA resistance, their impact on DAA in vitro potency when evaluated in a GT-6a consensus replicon, and their ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…Analysis of GT6 NS3 from different subtypes identified a rare D168E polymorphism not described as modifying anti-NS3 susceptibility and no such polymorphism was found on our patient sequences. Our findings and reports from the literature are thus quite reassuring in term of second generation anti-NS3 efficacy on all GT6 subtypes, with no evidence for polymorphism significantly modifying DAA potency 11 .…”
Section: Accepted Articlesupporting
confidence: 78%
See 3 more Smart Citations
“…Analysis of GT6 NS3 from different subtypes identified a rare D168E polymorphism not described as modifying anti-NS3 susceptibility and no such polymorphism was found on our patient sequences. Our findings and reports from the literature are thus quite reassuring in term of second generation anti-NS3 efficacy on all GT6 subtypes, with no evidence for polymorphism significantly modifying DAA potency 11 .…”
Section: Accepted Articlesupporting
confidence: 78%
“…Indeed, McPhee et al report in vitro high level of resistance to velpatasvir in replicons carrying both NS5A L28T/R30S RAS, a common motif found exclusively in subtype 6f and also found in one of our patients 11 . We believe awareness should be promoted when treating uncommon subtypes that may not be as susceptible to the so-called "pan-genotypic" current combinations, even though current real-world efficacy data are very reassuring.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Indeed, most data on DAA efficacy to date have been derived from clinical trials conducted in Western countries, where GT6‐HCV is rare and only few data sets exist for countries such as Cambodia and Vietnam with higher GT6 prevalence. Few in vitro studies have clearly identified significant difference in DAA potency according to GT6 subtypes or even selection of resistance . Importantly, while their data validate DAA activity on subtype 6a prototypes, efficacy on less frequent subtypes is missing despite great polymorphism on residues known to influence DAA efficacy .…”
Section: Introductionmentioning
confidence: 99%